2022
DOI: 10.3389/fcvm.2022.936651
|View full text |Cite
|
Sign up to set email alerts
|

Online searches for SGLT-2 inhibitors and GLP-1 receptor agonists correlate with prescription rates in the United States: An infodemiological study

Abstract: Several clinical trials have demonstrated that many SGLT-2 inhibitors (SGLT2i) and GLP-1 receptor agonists (GLP-1 RA) can reduce the risk of cardiovascular events in patients with Type 2 diabetes and atherosclerotic cardiovascular disease. Recent reports indicate an underutilization of new cardiometabolic drugs, including SGLT2i and GLP-1 RA. We aimed to evaluate the use of online search volumes to reflect United States prescription rates. A repeated cross-sectional analysis of Google search volumes and corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
Order By: Relevance
“… 16 Between January 2016 and December 2021, prescriptions for SGLT2 inhibitors increased by 115%. 17 With the recent Food and Drug Administration approval of SGLT2 inhibitors for heart failure with midrange ejection fraction in 2022, the prescription frequency is thought to increase further in the coming years. With the increasing use, it is important to be mindful of the yet-to-be-fully-understood adverse effects of these medications, such as pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Between January 2016 and December 2021, prescriptions for SGLT2 inhibitors increased by 115%. 17 With the recent Food and Drug Administration approval of SGLT2 inhibitors for heart failure with midrange ejection fraction in 2022, the prescription frequency is thought to increase further in the coming years. With the increasing use, it is important to be mindful of the yet-to-be-fully-understood adverse effects of these medications, such as pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2015 to 2020, 63.2 million prescriptions for SGLT-2 inhibitors were dispensed, with annual prescriptions doubling over the 6 years 15. Another study reported a 114.6% increase in prescription rates between 2016 and 2021 16. This increase in SGLT-2 inhibitor use could be partially attributed to cardiologist interest after the EMPA-REG results.…”
Section: Epidemiologymentioning
confidence: 99%
“… 15 Another study reported a 114.6% increase in prescription rates between 2016 and 2021. 16 This increase in SGLT-2 inhibitor use could be partially attributed to cardiologist interest after the EMPA-REG results. The EMPA-REG Trial indicated cardiovascular benefit in heart failure with empagliflozin; subsequently, there has been a steady increase in the number of empagliflozin prescriptions (51.7% increase), while canagliflozin initiation trended down (75.1% decrease).…”
Section: Epidemiologymentioning
confidence: 99%
“…To date, no study compared the interest of Google users in different treatment methods for obesity. Previous papers using GT compared only bariatric surgery methods [ 10 , 11 ] or GLP-1 analogs [ 12 ]. We hypothesize that analysis of GT may present trends of the popularity of different methods: current surges and past fads.…”
Section: Introductionmentioning
confidence: 99%